2015
DOI: 10.3109/14397595.2015.1019962
|View full text |Cite
|
Sign up to set email alerts
|

Presence of enthesopathy demonstrated with ultrasonography in systemic sclerosis

Abstract: To the best of our knowledge, this is the first study showing the presence of enthesopathy in patients with SSc using US. Enthesopathy should be kept in mind in symptomatic patients with SSc; additionally, it can be easily identified with US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
4
9
0
Order By: Relevance
“…Articular involvement is a common feature of SSc and it is frequently underestimated [4,5]. In SSc, synovitis is the most common joint manifestation, but specific SpA-like alterations have also been described [8,10]. In this context, our data definitively confirm that enthesis alterations are common in SSc, affecting both upper and lower limbs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Articular involvement is a common feature of SSc and it is frequently underestimated [4,5]. In SSc, synovitis is the most common joint manifestation, but specific SpA-like alterations have also been described [8,10]. In this context, our data definitively confirm that enthesis alterations are common in SSc, affecting both upper and lower limbs.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, tenosynovitis of the hand was found in 27% of SSc patients, showing a mixed pattern of inflammatory and fibrotic changes [6]. In addition, other studies suggested that even knee and ankle tendons without sheath are altered in SSc patients [9] and that enthesopathy is more frequent in SSc patients than in healthy subjects [10]. Collectively, the bulk of data suggest that there are SpA-like articular manifestations in SSc, but only one study focussed on the prevalence of entheseal alterations in SSc patients and none on the pathologic alterations of the synovio-entheseal complex (SEC) in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SSc, especially those with the dcSSc, may have joint involvement (Avouac et al, 2010) and present enthesopathy (Kilic, Kilic, Akgul, & Ozgocmen, 2015). Proximal muscle weakness in the shoulder and hip-pelvic region is a common feature (Akesson, Fiori, Krieg, van den Hoogen, & Seibold, 2003;Clements et al, 1978).…”
mentioning
confidence: 99%
“…Kilic et al 25 conducted a cross-sectional single-centre study aimed to investigate the presence and distribution of enthesopathy in SSc. Patients with SSc had significantly higher Madrid sonographic enthesitis index (MASEI) scores than the healthy controls.…”
Section: Enthesitismentioning
confidence: 99%
“…There was a positive correlation between MASEI score and age, modified Rodnan skin score (mRSS) and severity of dyspnoea and a negative correlation with handgrip strength. 25 Terenzi et al 26 conducted a cross-sectional study which sought to estimate the prevalence of entheseal and synovio-entheseal complex (SEC) alterations in SSc. Glasgow Ultrasound Enthesis Scoring System (GUESS) was significantly higher in patients than in healthy controls, including lateral epicondylar common extensor tendon (CET) enthesis.…”
Section: Mskmentioning
confidence: 99%